PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN CANVA MIND MAPPING TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V DI SD NO. 4 DALUNG - Ni Gusti Ayu Putu Purnama Yanti; I Gusti Ngurah Triyana; I Nyoman Artana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Problem Based Learning (PBL) model is a learning model that emphasizes the active involvement of students in solving problems so that it can help improve conceptual understanding and critical thinking skills. The use of Canva mind mapping as a learning medium helps students understand the material through a more visual and structured presentation of information. This research is motivated by the low learning outcomes of fifth-grade Indonesian students at SD No. 4 Dalung. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Canva mind mapping on the learning outcomes of fifth-grade Indonesian students at SD No. 4 Dalung. This study uses a quantitative approach with a quasi-experimental type and a Nonequivalent Control Group Design. The study population was 52 students with a saturated sampling technique. Learning outcome data were obtained through pretest and posttest tests. The data were then analyzed using descriptive statistics and inferential statistics through normality tests, homogeneity tests, and Independent Samples t-Test tests. The results showed that the average posttest score of students in the experimental group reached 76.73, while the control group obtained an average of 65.96. The results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, so H₀ was rejected and H₁ was accepted. These findings indicate that the application of the Problem Based Learning (PBL) model assisted by Canva mind mapping has a significant influence on the Indonesian language learning outcomes of fifth-grade students at SD No. 4 Dalung.